Pemberdayaan Wanita Dalam Kreativitas Dan Keindahan Merangkai Money Bouquet - Nursruwening, Yohana; Widyandini, Wita; Laxmita, Natasia Anggi (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Community empowerment in training in making money bouquets, especially for women as active members of society, is very important, because that it can foster creativity regarding beauty and increase income. Because creating together can encourage the enthusiasm and motivation of women who want to always have ideas for innovation and easily adapt to various situations. The aim of this community service activity is to empower and increase the creativity of women, both housewives and young women, through training in making money bouquets so that it can be used as a business opportunity to increase family income. This training activity was carried out using a demonstration method through three stages of activity, namely: 1) Preparation stage, by conveying the objectives of the activity and introducing the tools and materials used; 2) Implementation stage, participants make money bouquets with guidance from the service team and resource persons; 3) Mentoring stage. The results of the training show that this training activity is an activity that has never been carried out before so that participants gain new knowledge and experience in producing products and their creations are in the form of money bouquets. The benefit of this activity is to increase participants' creativity, this can be seen from the enthusiasm and percentage of participants who attended and took home the results of their creations in making money bouquets of 90%, only less than five participants did not complete their work.